2021
DOI: 10.1159/000513527
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Processing Sensitivity Predicts Individual Differences in Resting-State Functional Connectivity Associated with Depth of Processing

Abstract: <b><i>Background:</i></b> Sensory processing sensitivity (SPS) is a biologically based temperament trait associated with enhanced awareness and responsivity to environmental and social stimuli. Individuals with high SPS are more affected by their environments, which may result in overarousal, cognitive depletion, and fatigue. <b><i>Method:</i></b> We examined individual differences in resting-state (rs) brain connectivity (using functional MRI) as a function of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 96 publications
4
25
0
3
Order By: Relevance
“…Sensory processing sensitivity has been linked with heightened activation of the insula, cingulate, inferior frontal gyrus, middle temporal gyrus, and the premotor area. These findings are consistent with aberrations in fMRI insula and cingulate responses that have been observed among individuals with eating disorders (Acevedo et al, 2021). Disentangling trait and state neurobiological factors complicates the interpretation of neuroimaging findings in the identification of neural circuits involved in differential susceptibility (Frank, 2013) (as does the impact of starvation).…”
Section: Brain Based Systems Of Sensitivity and Eating Disorderssupporting
confidence: 90%
See 2 more Smart Citations
“…Sensory processing sensitivity has been linked with heightened activation of the insula, cingulate, inferior frontal gyrus, middle temporal gyrus, and the premotor area. These findings are consistent with aberrations in fMRI insula and cingulate responses that have been observed among individuals with eating disorders (Acevedo et al, 2021). Disentangling trait and state neurobiological factors complicates the interpretation of neuroimaging findings in the identification of neural circuits involved in differential susceptibility (Frank, 2013) (as does the impact of starvation).…”
Section: Brain Based Systems Of Sensitivity and Eating Disorderssupporting
confidence: 90%
“…Neural models of sensitivity appear to involve similar alterations in functional connectivity of brain networks. Functional magnetic resonance imaging (fMRI) of individuals scoring higher on a measure of sensory processing sensitivity revealed higher resting state connectivity within the ventral attention, dorsal attention, and limbic networks, as well as higher connectivity in the default mode network between the hippocampus and the precuneus as well as the insula and the inferior parietal lobe compared to individuals who scored lower on this measure (Acevedo et al, 2021). Consistent with the phenotypic characteristics of attentional control, depth of processing, and memory consolidation, these patterns in neural networks may contribute to heightened sensory processing (Acevedo et al, 2021).…”
Section: Brain Based Systems Of Sensitivity and Eating Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, research into the neural substrates of stimuli discrimination showed a higher activation in visual attentional areas (right claustrum, left occipitotemporal, bilateral temporal and medial and posterior parietal regions) for subtle decisions in high SPS individuals 24 . Other research indicated that SPS individuals can show higher activations in brain regions involved in awareness and empathy (insula, inferior frontal gyrus), memory, and self-other processing (i.e., premotor area, cingulate, medial and dorsolateral prefrontal cortex) 24 – 27 and enhanced functional connectivity among attentional and limbic network in resting state 28 . These results are consistent with highly sensitive persons being more aware and more intensely affected by others’ moods 9 and having an enhanced depth of processing 14 .…”
Section: Discussionmentioning
confidence: 99%
“…This brain structure is described as a center of sensory awareness; it is associated with limbic functions and self-referential processing ( Fan et al, 2011 ; Acevedo et al, 2014 ). High sensory processing sensitivity is associated with activation of the brain in regions responsible for deep processing, memory and psychophysiological regulation in response to emotive stimuli ( Acevedo et al, 2017 , 2021 ). Using functional magnetic resonance imaging (fMRI), Acevedo et al (2017) analyzed brain activity due to sensory processing sensitivity exposure to negative, positive or neutral stimuli revealed that highly sensitive sensory processing was related to increased activation of the hippocampus, the hypothalamus, the entorhinal area, and the temporal gyri; it was also related to decreased activation of the inferior parietal area.…”
Section: Introductionmentioning
confidence: 99%